UJI BIOAKTIVITAS PADA EKSTRAK KASAR ETANOL, FRAKSI n-HEKSAN, ETIL ASETAT DAN ETANOL-AIR DARI DAUN ANDONG (Cordyline terminalis Kunth) - Ritson Purba; Enos Tangke Arung; Teddy Tranoto (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2014)
Phytochemical, brine shrimp lethality and antibacterial activity tests in each fraction from Andong leaves extract(Cordyline terminalis Kunth) that came fromUnmul Samarinda botanical garden, Kalimantan Timur has been carried out. The leaf was extracted with ethanol andconcentrated by using rotaryevaporator. The crudeethanol extract was fractioned with n-hexane, and ethyl acetate. Based on the secondary metabolites phytochemical test of the Cordyline terminalis Kunth leaves show that crudeethanol extract is contain phenol, saponin and steroid.n-hexane fraction iscontain steroid.Ethylacetate fraction is contain phenol and steroid. And ethanol-water fraction is contain phenol and saponin. Brine shrimp lethality test exhibit mortality rate of Artemiasalina (L) by Probit SAS analysis to determine lethal concentration 50% (LC 50 ) value. The test showed that the most active wascrudeethanol extract with LC 50 value of 26.8788 ppm. Antibacteria activity test of extracts for Bacillus cereus bacteria (positiveGram) andEscherichia coli (negativeGram) were carried out by paper disk method. The test showed that the most active were ethyl acetate extract with minimum inhibitor consentration of 2-10% which clear zone diameter was 6,4 mm on Bacillus cereus bacteria and 6 mm on Escherichia colibacteria.Keywords: Phytochemical, Antibacteria activity, LC 50